Short Communication: MADS-box genes expression in seedlings of Elaeis guineensis Jacq. resistance to Ganoderma boninense (Biodiversitas Journal of Biological Diversity, 2020)
Abstract. Hayati R, Lisnawita, Munir E, Basyuni M. 2020. Short Communication: MADS-box genes expression in seedlings of Elaeis guineensis Jacq. resistance to Ganoderma boninense. Biodiversitas 21: 5805-5810. Advances in molecular technology were allowed the molecular studies of the flowering genes to expected to be used to predict oil palm (Elaeis guineensis) fruit production. This study aims to identify the genetic structure associated with flowering genes, belonging to the MADS-box gene family of E. guineensis to Ganoderma boninense susceptible and resistance types. Different length of expression genes was identified for each population displayed the single band pattern. On the basis of UVITEC-1D methods, all populations (RA, RS, SS, and SA) detected overall expression in primer EGGLO and EGDEF. Moreover, several populations (SS, SA, RA) were not expressed in primer EGSQUA, EGAGL2, and EGAG. Based on the GENEALEX results, 5 sets of MADS-box family markers showed Na values were 2.20 to 3.00, and He values were 0.40–0.67. High polymorphism information content (PIC > 0.50) was found in Resistance Asymptomatic (RA) and Susceptible Asymptomatic (SA) populations (PIC = 0.82). The phylogenetic tree described clustering for populations based on genetic distances. The dendrogram was constructed with two cluster groups. The first cluster was described as resistance asymptomatic and symptomatic population. Furthermore, the second cluster consisted of two clustering susceptible asymptomatic and symptomatic populations, separately. Several oil palm genes resistant symptomatic and asymptomatic was found in one cluster, similarly in susceptible symptomatic and asymptomatic grouped more closely. This phenomenon is likely to be the sampling rate and the addictive nature of parent crossing derivatives.
Keywords: Elaeis guineensis, GENEALEX, MADS-box gene expression, oil palm, PIC